Rezim Baru Monarki Thailand: Antara Darurat Militer Dan Kesejahteraan Sosial Di Wilayah Selatan - Bayu Mitra A. Kusuma; Theresia Octastefani (Universitas Islam Malang, 2019)
Muslim communities in Southern Thailand have experienced in discrimination among in economic, social, and politics. This condition has even occurred in the last seven decades under King Bhumibol Adulyadej, who was known to be wise king. Basically, King Bhumibol as the head of state always stated that social welfare approace is the best way to solve the problem, but almost every Thai Prime Minister as the head of government unfortunately always uses a militaristic approach that triggers social resistance. Since King Bhumibol died, Thailand has faced with the potential crisis for two reasons. First, Maha Vajiralongkorn as a successor, he is considered have different charisma with his father because he is very glamorous and have controversial lifestyle. Secondly, the absence of King Bhumibol, who has been a counterweight to the state made the Thai military more often coups. This conditions give impact to Muslim communities in the South who always live with uncertainty condition with two possibilities. First, Muslim communities have a better life under the new monarchy regime with social welfare and humanity approaches. Secondly, the condition of the Muslim communities will remains stagnant under the controversial king with continued by martial law.